Analisis Share and Growth serta Indeks Kemampuan Keuangan pada Kabupaten/ Kota di Kalimantan Timur - Nazmi, Fadilatun; Sundari; Margiatin, Sri (Soratekno Publisher, 2026)
The financial performance of a region can serve as an indicator of the local government’s overall performance. One methode of analyzing such financial performance is by examining financial ratios based on the Regional Revenue an Expenditure Budget (APBD) that has been determined and implemented. This study aims to measure the financial performance of the local governments of the regencies and cities surrounding the New Capital City (IKN) in East Kalimantan Province during the periode 2020 – 2024. Several ratios used in the analysis of financial performace include Share and Growth, rhe Regional Financial Capability Maping, and the Financial Capability Index (IKK). Based on the financial performance analysis conducted over five years for the four regencies and cities supporting the New Capital City (IKN), the following results were obtained. The share ratio of Samarinda City during the five-year period 2020 – 2024 falls under the low category. The share ratios of Penajem Paser Utara Regency and Kutai Kartanegara Regency fall under the very low category. Meanwhile, Balikpapan City and Penajem Paser Utara Regency falls under the low category. Kutai Kartanegara Regency shows a moderate growth ratio, while Balikpapan City is categorized as very low. Based on the Share and Growth analysis within the Regional Financial Capability Maping, two regions are positioned in Quadrant IV (Samarinda City and Penajem Paser Utara Regency), one region in Quadrant II (Kutai Kartanegara Regency), and one region in Quadrant III (Balikpapan City). Based on the Financial Capability Index (IKK), three regions fall under the high financial capability category, while one region is categorized as moderate.